Invitro analysis of antifungal effects of botanicals on sclerotinia sclerotiorum causing white mold disease - Gyanwali, Prashant; Khanal, Renuka; Pokharel, Netra Prasad; Tharu, Bhuwan; Koirala, Rajan; Paudel, Sandesh; Paudel, Rajan (Agriculture and Food Sciences Research, 2023)
White mold, Sclerotinia sclerotiorum, is a devastating fungal plant pathogen that has affected many crop species worldwide. Using chemicals to control the disease has been practiced over the years, whose prolonged application has negatively impacted the environment, thus finding an organic solution is crucial. The analysis quantifies the effect of 5 different local plants that have been proven to have fungicidal properties; Artemisia vulgaris L., Azadirachta indica L., Zingiber officinale Roscoe, Allium sativum L., and Lantana camara L. Poisoned food technique was used to study the inhibition effect, carried out by inoculating and growing the fungus on PDA media infused with botanical extracts. The data of mycelial mat diameter was recorded till the control plates were fully occupied. The growth-inhibiting capacity was found as 100% by Allium sativum, 28% & 43% by Azadirachta indica, 22.44% & 44% by Zingiber officinale, and 16.33% & 8.55% by Lantana camara at 10% and 20% concentrations respectively. Only a slight difference between the overall inhibition effect of the two concentrations was found with 37.22% inhibition by 20% concentration and 33.38% inhibition by 10% concentration. No inhibition effect was observed from Artemisia vulgaris which could be due to heat neutralization of the active constituent during sterilization. Further research needs to be conducted using the botanical with different sterilization techniques. This in-vitro study identified garlic as a critical antifungal alternative to conventional fungicides. Field experiments need to be done to prove its effectiveness.